2017
DOI: 10.1016/j.diabet.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

An extended fatty liver index to predict non-alcoholic fatty liver disease

Abstract: This study has provided novel data confirming that the OGTT-derived fold-change TG and 2-h glucose level, together with the rs738409 C>G SNP in PNPLA3, allow calculation of an extended FLI that considerably improves its power to predict NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…In addition, a very recent study proposed the extended FLI which significantly improves the power of the FLI to predict NAFLD [31]. Namely, the authors demonstrated that the fold-change of plasma triglycerides during a 2 h oral glucose tolerance test and 2 h glucose levels, together with the rs738409 C > G single nucleotide polymorphism in PNPLA3 may improve the power of the widely used FLI for NAFLD prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a very recent study proposed the extended FLI which significantly improves the power of the FLI to predict NAFLD [31]. Namely, the authors demonstrated that the fold-change of plasma triglycerides during a 2 h oral glucose tolerance test and 2 h glucose levels, together with the rs738409 C > G single nucleotide polymorphism in PNPLA3 may improve the power of the widely used FLI for NAFLD prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the RESMENA diet had a positive effect on body weight by reducing android fat mass—a body region which has been commonly associated with hepatic steatosis [ 24 ]. On the other hand, current research has focused on identifying biomarkers to predict NASH or NAFLD [ 25 , 26 ]. In this context, Bedogni et al (2006) designed a simple scoring system named FLI which includes TG, GGT, BMI, and WC, and it is easily calculated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FLI score, for example, is widely used as a predictor for NAFLD and metabolic syndrome [21,22] and for evaluating the effect of different treatment methods [23]. However, the FLI is still under investigation, and researchers continue to adjust how it is calculated to further improve the reliability [24]. Since the FLI also contains waist circumference, it is at risk for the abovementioned sources of error.…”
Section: Discussionmentioning
confidence: 99%